Enhancing Employability in the Digital Era: A Case Study of Online Workers Through the Lens of Contemporary Islamic Economic Law - Muhammad Ali Adriansyah; Seger Handoyo; Hendro Margono; Sheikh Adnan Ahmed Usmani; Dian Dwi Nur Rahmah (MILRev: Metro Islamic Law Review, 2025)
The digital era has changed the workforce significantly, especially with the rise of online-based jobs. This study aims to analyze the enhancement of online workers' employability through the perspective of contemporary Islamic Economic Law. The research employs a qualitative approach with a case study of online workers across various sectors. The findings indicate that digitalization has expanded job opportunities and introduced challenges such as income instability and a lack of legal protection. From the perspective of Islamic Economic Law, principles of justice, balance, and ethics in transactions play a crucial role in ensuring the sustainability and well-being of online workers. Therefore, appropriate regulations aligned with Islamic economic principles are needed to promote fairness and welfare for workers in the digital era. The main contribution of this study is to provide new insights into the application of Islamic Economic Law principles in the context of digital employment and offer policy recommendations to enhance the well-being of online workers. Additionally, this research contributes to developing Islamic digital economy literature and serves as a foundation for more inclusive and fair regulations for workers in the digital age.